ANALYSIS OF THE DYNAMICS OF BIO-CORRELATES OF PSYCHOLOGICAL STRESS INDICATORS IN FUTURE SHIPBOARD SPECIALISTS (Psychology Travelogs, 2023)
The article presents the results of an empirical study of the dynamics of biological correlates of psychological stress indicators in future shipboard specialists. It is noted that the psychological state is a relatively time-limited adjustment of the human psyche, which affects the course of mental processes and the manifestation of personality traits, increases or decreases the activity of mental activity over a certain period of time, determines the ability to work, readiness to overcome workloads, and even the ability of an individual to mobilise at the right time. Under the influence of mental stress, a ship's specialist working in extreme conditions undergoes significant changes in the cardiovascular and respiratory systems of the body. Therefore, the identification of these patterns is an important link in the work on the formation of his stress resistance.As you know, heart rate and pulse blood pressure are the main indicators of the functional state and activity of the entire cardiovascular system. It has been empirically established that during exercise with varying amounts of exertion, pulse arterial pressure changes in proportion to the volume of blood ejected by the heart during each systole and can reach ultra-high values above 100 millimetres of mercury. In this case, the normal reaction of the body is to return to baseline values within 5 minutes after the end of exercise. The absence of such a reaction indicates an increased level of cortisol in the blood, which, in turn, reflects a person's stressful state.
Keywords: biological correlates; psychological stress; future ship's specialists; physical exercises; stressful state